As a legal entity of limited partner (Journal of actual problems of jurisprudence, 2019)
In this article, the author considered legal entity, including some features LLP. and makes its conclusions. The inference processused rules of law and methods use it, shows it in theory and practical solution.Keywords: legal person, limited partner, stock company, rights and duties, commercial and non-commercial legal entities, state,proprietorship, organizational documents, constitution.